p38 MAPK regulates IL-1β induced IL-6 expression through mRNA stability in osteoblasts - Patil, Chetan; Zhu, Xinsheng; Rossa Júnior, Carlos [UNESP]; Kim, Young Joon; Kirkwood, Keith L. (My University, 2004)
Osteoblast-derived IL-6 functions in coupled bone turnover by supporting osteoclastogenesis favoring bone resorption instead of bone deposition. Gene regulation of IL-6 is complex occurring both at transcription and post-transcription levels. The focus of this paper is at the level of mRNA stability, which is important in IL-6 gene regulation. Using the MC3T3-E1 as an osteoblastic model, IL-6 secretion was dose dependently decreased by SB203580, a p38 MAPK inhibitor. Steady state IL-6 mRNA was decreased with SB203580 (2 μM) ca. 85% when stimulated by IL-1β (1-5 ng/ ml). These effects require de novo protein synthesis as they were inhibited by cycloheximide. p38 MAPK had minor effects on proximal IL-6 promoter activity in reporter gene assays. A more significant effect on IL-6 mRNA stability was observed in the presence of SB203580. Western blot analysis confirmed that SB203580 inhibited p38 MAP kinase, in response to IL-1β in a dose dependent manner in MC3T3-E1 cells. Stably transfected MC3T3-E1 reporter cell lines (MC6) containing green fluorescent protein (GFP) with the 3′untranslated region of IL-6 were constructed. Results indicated that IL-1β, TNFα, LPS but not parathyroid hormone (PTH) could increase GFP expression of these reporter cell lines. Endogenous IL-6 and reporter gene eGFP-IL-6 3′UTR mRNA was regulated by p38 in MC6 cells. In addition, transient transfection of IL-6 3′UTR reporter cells with immediate upstream MAP kinase kinase-3 and -6 increased GFP expression compared to mock transfected controls. These results indicate that p38 MAPK regulates IL-1β-stimulated IL-6 at a post transcriptional mechanism and one of the primary targets of IL-6 gene regulation is the 3′UTR of IL-6.
Keywords: ARE; Gene expression; GFP; IL-1β; IL-6; MRNA Stability; Osteoblasts; p38 MAPK; 4 (4 fluorophenyl) 2 (4 methylsulfinylphenyl) 5 (4 pyridyl)imidazole; cycloheximide; green fluorescent protein; interleukin 1beta; interleukin 6; lipopolysaccharide; messenger RNA; mitogen activated protein kinase p38; synaptophysin; tumor necrosis factor alpha; animal cell; bone turnover; cell strain; cell strain MC 3T3 E1; cell strain MC6; controlled study; cytokine release; dose response; gene control; genetic analysis; genetic transfection; mouse; nonhuman; osteoblast; osteoclast; osteolysis; priority journal; protein expression; protein processing; protein synthesis; publication; regulatory mechanism; reporter gene; RNA stability; steady state; Western blotting; 3' Untranslated Regions; Animals; Base Sequence; Cell Line; Enzyme Inhibitors; Gene Expression Regulation; Genetic Vectors; Interleukin-1; Interleukin-6; Mice; Molecular Sequence Data; p38 Mitogen-Activated Protein Kinases; Promoter Regions (Genetics); Recombinant Proteins; RNA Stability; RNA, Messenger; Signal Transduction